Factors Associated with the Decline of Kidney Function Differ among eGFR Strata in Subjects with Type 2 Diabetes Mellitus - Shu Meguro; Masuomi Tomita; Yusuke Kabeya; Takeshi Katsuki; Yoichi Oikawa; Akira Shimada; Toshihide Kawai; Hiroshi Itoh; Yoshihito Atsumi (International Journal of Endocrinology)
Introduction. There is no report about risk factors for renal deterioration according to the clinical stage, divided by the estimated glomerular filtration rate (eGFR) in type 2 diabetes. Materials and Methods. We evaluated the factors correlated with the annual eGFR decline in 1303 subjects with type 2 diabetes whose eGFR was ≥30 mL/min/1.73 m2. eGFR strata were defined by baseline eGFR value as follows: stratum 1: ≥90, stratum 2: ≥60, <90, and stratum 3: ≥30, <60. Results. The annual eGFR decline was 2.3±5.4 mL/min/1.73 m2 in overall subjects. Multiple linear regression analysis demonstrated that age, male sex, systolic blood pressure, logarithmically transformed albumin excretion rate (AER), eGFR strata, and hemoglobin concentration were significantly correlated with the annual eGFR decline. When stratified by eGFR, the factors that showed a significant correlation were different among eGFR strata. AER was significantly correlated with annual eGFR decline in all eGFR strata. Hemoglobin concentration showed a significant correlation only in the advanced eGFR stratum. Conclusion. The factors correlated with the annual eGFR decline were different among eGFR strata in type 2 diabetes mellitus, and hemoglobin concentration and AER were important factors for renal deterioration, especially in the advanced eGFR stratum.